Decellularized human chorion membrane as a novel biomaterial for tissue regeneration - Frazão, Laura Passos Morgado Franco (2020)
Although some placenta-derived products are already used for tissue regeneration, the human chorion membrane (HCM) alone has been poorly explored. In fact, just one study uses decellularized HCM (dHCM) with native tissue architecture (i.e., without extracellular matrix (ECM) suspension creation) as a substrate for cell differentiation. The aim of this work is to fully characterize the dHCM for the presence and distribution of cell nuclei, DNA and ECM components. Moreover, mechanical properties, in vitro biological performance and in vivo biocompatibility were also studied. Our results demonstrated that the HCM was successfully decellularized and the main ECM proteins were preserved. The dHCM has two different surfaces, the reticular layer side and the trophoblast side; and is biocompatible both in vitro and in vivo. Importantly, the in vivo experiments demonstrated that on day 28 the dHCM starts to be integrated by the host tissue. Altogether, these results support the hypothesis that dHCM may be used as a biomaterial for different tissue regeneration strategies, particularly when a membrane is needed to separate tissues, organs or other biologic compartments.